Sidney Blatt's Contributions to Personality Assessment. Issue 1 (2nd January 2016) - Auerbach, John S.
ABSTRACT: Over a long, distinguished career, Sidney Blatt contributed to theory and research in personality development, personality assessment, and psychotherapy. Best known for his 2-configurations model of personality and author or co-author of more than 250 articles and 18 books and monographs, Blatt was also a master clinician, a psychoanalyst who was awarded the 1989 Bruno J. Klopfer Award by the Society for Personality Assessment (SPA) for his contributions to both self-report and performance-based assessment. He was also the president of SPA from 1984 to 1986. This special series contains papers by writers who participated in all aspects of Blatt's contributions to personality assessment, both self-report and performance-based. Topics covered include Blatt's 2-configurations model of personality, development, and psychopathology; boundary disturbance and psychosis in performance-based assessment; the interaction of gender and personality on narrative assessments; and the Object Relations Inventory and differentiation relatedness, especially as these relate to therapeutic outcome.